(3eSfO GHf GdLYOs - (3CHh GdMSf Ydj Hf GdLYO Hf YHjO GdLhgQj GdHZOGOj, GHf GdLYO,J (B230 (3g` s ((3GdMGaX eMHO GdOjf GHf GdfLGQ s)
(3ChdgG (B:s
(3jHJOF HChd GdcJGH s
(3BNQgG (B:s
(3hjfJgi HCNHGQ efUhQ s
(3GdfSNI HgG MhGTs
(3YdjgG SeGY eDQN HSfI (B463(3g`s
(3hBNQ HJGQjN (B528(3g`s
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdMOjK h GdeUWdMs